Analisis Faktor-Faktor yang Mempengaruhi Peran Perempuan Tani Dalam Usahatani Jagung Pada Sistem Pertanian Lahan Kering di Kecamatan Pujut Kabupaten Lombok Tengah - Dm. Ali, Miftahul Khairat; Hayati, Hayati; Muktasam, Muktasam (Universitas Mataram, 2025)
The purpose of this study is to identify the factors influencing the role of women farmers in maize farming within the dryland agricultural system in Pujut District, Central Lombok Regency. Two villages, Mertak and Sukadana, were selected as research locations, as both have extensive dryland areas suitable for maize cultivation. This study employs a descriptive method. To determine the respondents,